The Impact of Listening Comprehension on Reading Comprehension: A Correlational Research - Hasim, Okta Rianti; Hendrety, Yuyun; Ria, Nita (CV. Doki Course and Training, 2024)
The aim of this research was to find out whether or not there was any correlation between students reading comprehension and students listening comprehension. The population was the tenth-grade students with the total 630 students from 14 classes at SMA N 10 Palembang. To the sample of this research, intake sampling technique was implemented. There were 90 students as a sample from class X.7 and X.8. The data were selected from students reading comprehension and students listening comprehension. In analysing the data, correlation analysis, regression analysis and normality test was used. Based on the statistical, it was found that the correlation coefficient or the R-value (0.000) with significant coefficient (p-value) was 0.422, which was higher than 0.05. It means that significant value (2-tailed) was higher than alpha value (0.422> 0.05). It could be concluded that there was a significant correlation between students' reading comprehension and listening skill. Since the Pearson correlation coefficient was 0.000, it indicated that there was correlation between students' reading. Also, for the contribution of listening comprehension to reading comprehension it was only 17.8%. It means that listening comprehension has no influence to reading comprehension. In conclusion, the findings indicate that students who have high listening comprehension does mean that they will also have good reading comprehension. Also, reading comprehension can be used to help listening skills because listening is the ability to capture sounds, complete, speak, syntax, jargon, and obtain data.